Molecular dynamics of fibric acids - Miller, Chad; Schildcrout, Steven; Mettee, Howard; Balendiran, Ganesaratnam (European Journal of Chemistry, 2022)
1H- and 13C-NMR chemical shifts were measured for four fibric acids (bezafibrate, clofibric acid, fenofibric acid, and gemfibrozil), which are lipid-lowering drugs. Correlation is found with DFT-computed chemical shifts from the conformational analysis. Equilibrium populations of optimized conformers at 298 K are very different when based on computed Gibbs energies rather than on potential energies. This is due to the significant entropic advantages of extended rather than bent conformational shapes. Abundant conformers with intramolecular hydrogen bonding via five-member rings are computed for three fibric acids, but not gemfibrozil, which lacks suitable connectivity of carboxyl and phenoxy groups. Trends in computed atom-positional deviations, molecular volumes, surface areas, and dipole moments among the fibric acids and their constituent conformations indicate that bezafibrate has the greatest hydrophilicity and fenofibric acid has the greatest flexibility. Theoretical and experimental comparison of chemical shifts of standards with sufficient overlap of fragments containing common atoms, groups, and connectivity may provide a reliable minimal set to benchmark and generate leads.